Mechanisms of electron transfer to insoluble terminal acceptors in chemoorganotrophic bacteria - I. A. Samarukha (The Ukrainian Biochemical Journal, 2014)
The mechanisms of electron transfer of association of chemoorganotrophic bacteria to the anode in microbial fuel cells are summarized in the survey. These mechanisms are not mutually exclusive and are divided into the mechanisms of mediator electron transfer, mechanisms of electron transfer with intermediate products of bacterial metabolism and mechanism of direct transfer of electrons from the cell surface. Thus, electron transfer mediators are artificial or synthesized by bacteria riboflavins and phenazine derivatives, which also determine the ability of bacteria to antagonism. The microorganisms with hydrolytic and exoelectrogenic activity are involved in electron transfer mechanisms that are mediated by intermediate metabolic products, which are low molecular carboxylic acids, alcohols, hydrogen etc. The direct transfer of electrons to insoluble anode is possible due to membrane structures (cytochromes, pili, etc.). Association of microorganisms, and thus the biochemical mechanisms of electron transfer depend on the origin of the inoculum, substrate composition, mass transfer, conditions of aeration, potentials and location of electrodes and others, that are defined by technological and design parameters.